The Effectiveness of the Talking Stick Method in Improving Students' Speaking Skill at Ma Uswatun Hasanah - Margaretha, Oktavia; Islam, Muhammad Hifdil; Kholili, Achmad (International Journal of English Education and Linguistics (IJoEEL), 2024)
Despite several studies on speaking skills in the EFL context, little attention has been attracted to investigating the effectiveness of the talking stick method on speaking skills. This study examines the effectiveness of the talking stick method in improving students' speaking skills at MA Uswatun Hasanah. The study used quantitative methods and interviews to gain a better understanding of the effectiveness of this method in classroom learning. The study used a simple random sampling technique and a one-group pre-test and post-test design. This study uses subjective tests in the form of read-aloud tests as an instrument to take pretest and posttest data. Likewise, the data collection methods used are observation, interviews to strengthen the data obtained from subjective tests. The mean post-test score (49.83) was higher than the pre-test score (42.87), indicating that the talking stick technique had a positive impact on the speaking ability of students at MA Uswatun Hasanah in the 2023–2024 academic year. The results showed that the talking stick technique had a significant positive impact on the speaking ability of students at MA Uswatun Hasanah.